PREDIKSI PEMBERIAN KELAYAKAN PINJAMAN DENGAN METODE FUZZY TSUKAMOTO - Nurul Ajeng; Bety Wulan Sari; Donni Prabowo (Information System Journal, 2020)
Sentra Gadai is a place to borrow in Yogyakarta. Every day giving loans to customers. In granting a loan the Senta Gadai has a condition that is a loan size of 50% of the collateral price. If the loan is more than 50%, the Sentra Gadai sometimes still hesitate to provide the loan. The Loan Eligibility Prediction System is used to help the Sentra Gadai in making decisions by providing alternative estimates in determining the feasibility of borrowing by the customer. This prediction system uses Tsukamoto's fuzzy method in estimating the feasibility of loans to customers by having several criteria such as the duration of the loan, the price of the guarantee and the condition of the goods. This prediction system is based on desktop because it is only used by the Sentra Gadai and not to the public with the Java programming language and database using phpMyAdmin. Keywords : Prediction System, Loan,Fuzzy Tsukamoto